2000
DOI: 10.1046/j.1365-2567.2000.00025.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cytokine production by immunological and foreign body multinucleated giant cells

Abstract: SUMMARYMultinucleated giant cells (MGC) are a common feature of granulomas. The mechanism of their formation has been studied extensively, but their function has not been completely characterized. A new method for the in vivo production of MGC was developed involving subcutaneous injection of microscopic nitrocellulose particles with adsorbed mycobacterial antigens into the footpads of sensitized BALB/c mice (immune [I]-MGC), or by nitrocellulose administration to non-sensitized mice (foreign body [FB]-MGC). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
60
1
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 22 publications
(44 reference statements)
2
60
1
4
Order By: Relevance
“…According to many authors, granulomas represent a successful T cell-dependent immune response (Sheffield 1990;Murray and Nathan, 1999;Hernandez-Pando et al, 2000). Granulomas typically require an antigen-specific immune response mediated by mononuclear cells, develop relatively slow and persist for extended periods, and are more likely to be provoked by intra rather than extracellular pathogens (McElrath et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…According to many authors, granulomas represent a successful T cell-dependent immune response (Sheffield 1990;Murray and Nathan, 1999;Hernandez-Pando et al, 2000). Granulomas typically require an antigen-specific immune response mediated by mononuclear cells, develop relatively slow and persist for extended periods, and are more likely to be provoked by intra rather than extracellular pathogens (McElrath et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that bovine pericardium and Teflon are associated with predominantly mononuclear inflammatory infiltrations in the adjacent tissue and the induction of a graft-versus-host type immunological response. These formations constitute an active source of cytokines, which may start and maintain inflammatory processes induced by foreign substances in the organism [11][12][13][14][15].…”
Section: Commentsmentioning
confidence: 99%
“…However, at sites of resistant infectious agents (e.g., tuberculosis) or poorly bio-degradable tissue irritants (i.e., foreign bodies), macrophages remain activated and fuse to form multinucleate giant cells (MGCs) that can persist for weeks or months surrounding the unresolved site. At these sites, MGCs actively phagocytose debris and can acutely produce proinflammatory cytokines (interleukin-1 ␣ , TNF-␣ ) until the insult is either cleared by phagocytosis or encapsulated (12).…”
mentioning
confidence: 99%